Changes of Composition and Angiotensin I-Converting Enzyme-Inhibitory Activity During Douchi Fermentation. Issue 11 (1st November 2016) - Wang, Hui; Meng, Fanjia; Yin, Lijun; Cheng, Yongqiang; Lu, Anxiang; Wang, Jihua
Abstract : Douchi is a fermented soybean food, which is popular in China. Composition and angiotensin I-converting enzyme-inhibitory activity of Douchi fermented with Mucor wutungkiao were studied in this work. The results showed that the nutritional potency of protein, fat, and soluble polysaccharide was improved in Douchi fermentation. The angiotensin I-converting enzyme-inhibitory activity of Douchi that ripening for 2 weeks showed the highest angiotensin I-converting enzyme-inhibitory activity. Then this sample was purified with Sephadex G-25 gel chromatography, and the amino acids and angiotensin I-converting enzyme-inhibitory activity of the purified fractions were studied. The results suggested that hydrophobic amino acids were assumed to cause the main increase of the angiotensin I-converting enzyme-inhibitory activity in Douchi.